2023
DOI: 10.1210/jendso/bvad099
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Pancreatic β-Cell Physiology and Glucose Homeostasis in C57BL/6J Mice

Abstract: The importance of sexual dimorphism has been highlighted in recent years since the National Institutes of Health’s mandate on considering sex as a biological variable. While recent studies have taken strides to study both sexes side by side, investigations into the normal physiological differences between males and females are limited. In this study, we aimed to characterized sex-dependent differences in glucose metabolism and pancreatic beta cell physiology in normal conditions using C57BL/6J mice, the most c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 54 publications
4
5
0
Order By: Relevance
“…Several previous studies have demonstrated significant strain-specific differences in mice regarding insulin release ( 79 , 80 ), pancreas size and structure ( 81 ), and susceptibility to diabetes ( 79 84 ). However, our findings showing that female islets secrete more insulin that leads to a better glucose tolerance corroborate well both with human data ( 2 , 60 63 ) and several rodent studies ( 60 , 74 , 85 ). Additionally, a recent study demonstrated ( 74 ), also in the C57BL/6 background, that female islets respond with reduced Ca 2+ transients to glucose stimulation but increased β cell oscillatory responses compared with males, very similar to our previous ( 48 ) and current study.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Several previous studies have demonstrated significant strain-specific differences in mice regarding insulin release ( 79 , 80 ), pancreas size and structure ( 81 ), and susceptibility to diabetes ( 79 84 ). However, our findings showing that female islets secrete more insulin that leads to a better glucose tolerance corroborate well both with human data ( 2 , 60 63 ) and several rodent studies ( 60 , 74 , 85 ). Additionally, a recent study demonstrated ( 74 ), also in the C57BL/6 background, that female islets respond with reduced Ca 2+ transients to glucose stimulation but increased β cell oscillatory responses compared with males, very similar to our previous ( 48 ) and current study.…”
Section: Discussionsupporting
confidence: 92%
“…However, our findings showing that female islets secrete more insulin that leads to a better glucose tolerance corroborate well both with human data ( 2 , 60 63 ) and several rodent studies ( 60 , 74 , 85 ). Additionally, a recent study demonstrated ( 74 ), also in the C57BL/6 background, that female islets respond with reduced Ca 2+ transients to glucose stimulation but increased β cell oscillatory responses compared with males, very similar to our previous ( 48 ) and current study. Nevertheless, while under basal glucose conditions female islets secreted more insulin, the stimulated insulin release was higher in males ( 74 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Male mice were used because they have a higher β-cell mass and secrete more insulin in response to glucose than female mice and were therefore expected to display an enhanced response to IF 1 . 55 In conclusion, this study establishes that apoA-I restores insulin secretion in β-cells with disrupted cholesterol homeostasis by binding to an ectopic F1-ATPase β-subunit, internalizing into the cells and localizing to mitochondria where it decreases oxidative stress and enhances insulin secretion in response to glucose. Whether the observed increase in insulin secretion can be attributed to nuclear exclusion of pancreatic and duodenal homeobox 1, as reported previously, or whether it reflects improved processing of proinsulin to insulin and increased expression of the prohormone convertase 1/3 remains to be determined.…”
Section: Discussionsupporting
confidence: 57%